Communicating With the Audience in Mind - Robert Agunda (Journal of Applied Communications, 1989)
Agricultural communication is a very young discipline and its professionals are still defining their function. An important element that must guide us in our search for identity, however, is knowing who our primary audience really is. Is it the organizalions for which we work? Should we focus our attention on the farmers and agribusiness owners, many of whom are highly educated and have, for the most part, many ways of obtaining innovative informalion? Or should we more properly address the needs of those who are agriculturally illiterate, and whose main source of information about how agriculture affects their lives seems to be us, the agricultural communicators. This author argues that the "poor masses out there" must be our main audience and asks the question: Do we know how to reach them with the information they so vitally need?